THE STRUGGLE AGAINST TUBERCULOSIS IN THE TERRITORY OF MORAVA BANOVINA (Heritage, 2025)
This paper presents the efforts of the Banovina and local authorities in suppressing tuberculosis, as the most common infectious disease in the territory of the Morava Banovina. Considering that this disease was the result of mainly bad lifestyle habits and unhygiene, the way of life and diet of the population were also addressed. The paper was created on the basis of archival materials, as well as published statistical data of civilian and military provenance.
Keywords: Kingdom of Yugoslavia, Morava Banovina, tuberculosis, health care